PROCESSING REMOVABLE ORTHODONTIC APPLIANCE FOR SINGLE TOOTH ANTERIOR CROSSBITE USING EXPANSION SCREW - Rusdiana, Elly; Goenharto, Sianiwati; Nirmala Ratna Harda, Sasadhara; Wahjuni, Sri; Indiani, Sri Redjeki (Faculty of Vocational Studies, Universitas Airlangga, 2023)
Background: Anterior crossbite is a case that when upper anterior are positioned palatally than lower anterior teeth in centric occlusion. Orthodontic appliances using expansion screw could be solution for tooth anterior crossbite treatment. Purpose: To figure out the optimal fabrication process of orthodontic appliances in single tooth anterior crossbite case using expansion screw. Case analysis: Dental laboratory provided the maxillary dental appliance with single tooth anterior crossbite on teeth 21. Dental technician also received orthodontic appliance using expansion screw. Result: Orthodontic appliance design was Adams claps on teeth 16, 26, labial bow on teeth 13, 12, 11, 21, 22, 23. Additional posterior bite plane, also expansion screw was located on maxillary left first incisor, palatal section. Conclusion: Design and making orthodontic appliances using expansion screw begins with drawing design, positioning Adams clasps and labial bow sectional screw mini mounting, then acrylic packing. Final step was finishing polishing acrylic plate.